Child Mortality in Rural India - van der Klaauw, Bas (2012)
This paper focuses on infant and child mortality in rural areas of India. We construct a flexible duration model, which allows for frailty at multiple levels and interactions between the child's age and individual, socioeconomic, and environmental characteristics. The model is estimated using the Indian National Family and Health Survey 1998/1999. The estimation results show that socioeconomic and environmental characteristics have significantly different impacts on mortality rates at different ages. These are particularly important immediately after birth. The parameter estimates indicate that child mortality can be reduced substantially, particularly by improving the education of women, providing safe water, and reducing indoor air pollution caused by dirty cooking fuels. Finally, we still found substantial differences in mortality rates between states, which are associated with differences in schooling expenditures, female immunization, and poverty rates.